2021
DOI: 10.1002/pls2.10062
|View full text |Cite
|
Sign up to set email alerts
|

Processing and rheological behavior of cross‐linked polyethylene containing disulfide bonds

Abstract: Vitrimers are a new class of materials that consist of chemically cross‐linked networks that engage in thermoactivated associative exchange reactions. These exchange reactions can impart malleability, healing, and recyclability properties to thermosets. In this study, a one‐step protocol to prepare linear low‐density polyethylene (LLDPE) vitrimer‐like materials with disulfide exchange bonds via reactive blending is presented. The cross‐linking reaction of maleic anhydride‐grafted‐linear low‐density polyethylen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 31 publications
(42 reference statements)
1
36
0
Order By: Relevance
“…These include step-growth reactions between polymers made by free-radical polymerization (FRP) and small-molecule additives serving as cross-linkers. 60,61 Preparing dynamic networks with robust properties by exclusively addition-type polymerization methods, e.g., FRP and its variants 32,42,43,[48][49][50][51][52][62][63][64] or radicalbased reactive processing, [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79] is a relatively untapped approach in CAN technology. It is important that methods to develop CANs via FRP and radical-based reactive processing are investigated because many thermosets with limited recyclability, e.g., PEX, are synthesized by such methods.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…These include step-growth reactions between polymers made by free-radical polymerization (FRP) and small-molecule additives serving as cross-linkers. 60,61 Preparing dynamic networks with robust properties by exclusively addition-type polymerization methods, e.g., FRP and its variants 32,42,43,[48][49][50][51][52][62][63][64] or radicalbased reactive processing, [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79] is a relatively untapped approach in CAN technology. It is important that methods to develop CANs via FRP and radical-based reactive processing are investigated because many thermosets with limited recyclability, e.g., PEX, are synthesized by such methods.…”
Section: Introductionmentioning
confidence: 99%
“…Radical-based reactive processing to modify polymers with dynamic graing units has recently gained traction as a method by which commodity plastics may be upcycled into CANs with enhanced properties and reprocessability. [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79]85,86 Following the 2017 seminal study by Röttger et al 66 on the production of HDPE vitrimers by transesterication of boronic esters graed onto HDPE during reactive processing, a number of studies have been reported on polyethylene (PE) CANs. [67][68][69][70][71][72][73][74][75][76]78,79,85,86 However, few studies address the myriad of challenges that remain before the potential of PE CANs may be realized.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of LDPE vitrimers led to a material with reversible crosslinks. [ 24 ] While these works in the literature represent moderate success, there still is a need for simple, continuous, commercially scalable techniques to manage chemical crosslinks at the manufacturing stages.…”
Section: Introductionmentioning
confidence: 99%